An Empirical Investigation on the Association between Small and Medium Enterprises and the Economic Growth of Sri Lanka - Vijayakumar, S. (Trends Economics and Management, 2013)
Purpose of the article: SMEs play important role in both developed and newly industrialized countries in terms of boosting economic growth and alleviating poverty. Despite there are vast numbers of SMEs in Sri Lanka, people do not enjoy stable economic growth and good living standard so far. Therefore, the prime intension of this study is to find out the association between economic growth and SMEs in Sri Lanka and also nexus among the economic growth, poverty and SMEs. Methodology/methods: This study analyzes the impact of small and medium enterprises in the economic growth and poverty in addition to role of SMEs in consonance with employment generation and value added in Sri Lanka. The secondary data have been employed for the analysis. The simple multiple regression model was employed to analyze the data. Heteroskedasticity and serial correlation problems were detected with the help of statistical soft ware (E-views). Scientific aim: The aim of study is to scrutinize the association between economic growth and SMEs and the relationship among the economic growth, poverty and SMEs. It strived to bring about the general behavior of SMEs in Sri Lanka. Findings: The finding clearly shows that there is positive relationship between economic growth and SMEs but, impact of SMEs on economic growth is not significant in Sri Lanka. Even though the co-efficient of SMEs is 0.02 indicating that there is positive relationship between economic growth and SMEs, the impact of SMEs on economic growth is statistically insignificant. Another finding is that there is vast number of industrial establishments of SMEs in total establishments which do not significantly contribute to the employment generation and value added in Sri Lanka. Conclusions: Notwithstanding several literatures related to SMEs have articulated the fact that SMEs can play important role in boosting economic growth, employment generation, accumulation of capital and poverty reduction, this experience is not consistent with Sri Lanka. The output of this study clearly proves the conclusion that SMEs don’t play significant impact on economic growth of Sri Lanka while poverty has significant effects on economic growth. Furthermore, public private participation (PPP) is sine qua none to the effective promotion of SMEs which leads to economic growth and poverty reduction. Visionary government can launch effective PPP which is remedy for the successful promotion of SMEs and thereby boosting economic growth.
Keywords: small and medium enterprises; economic growth; employment; value added; Public private; Participation